Overview of the Functions of Ginger Rhizome (Zingiber officinale Roscoe), Black Cumin (Nigella sativa), and Pasak Bumi (Eurycoma longifolia Jack) in Male Infertility - Setyaningrum, Dyah Ayu Woro; Anggraini, Kirana (The Avicenna Medical Journal, 2023)
Background: More than 186 million individuals worldwide from Southeast Asian and African nations are affected by infertility, a common health issue, specifically among men. In Indonesia, the use of "jamu" or herbal preparations derived from a diverse variety of herbal sources remains a widely practiced therapeutic approach. Furthermore, the Research and Development Center of the Indonesian Ministry of Health conducted extensive investigations between 2012 and 2018, including 204 distinct plant species used as stimulants and fertility enhancers. Among the species extensively used by ethnic traditional healers are pasak bumi (Eurycoma longifolia Jack), Pimpinella alpina Kds or Pimpinella pruatjan Molk (purwoceng), ginger rhizome (Zingiber officinale Roscoe), and black cumin (Nigella sativa).Methods: This study was compiled as an overview of ten original articles from PubMed and Google Scholar using keywords related to the effects of ginger rhizome, black cumin, and pasak bumi on male infertility.Results: The three plants were useful for improving sperm parameters by antioxidant activity, and increasing the production of reproductive hormones.Conclusion:These plants had a potential role in treating and protecting male infertility by the antioxidant activities.